Unveiling Multidimensional Poverty in Jammu and Kashmir: Insights from Alkire Foster Method and NFHS-5 Data - Ali, Umar; Handoyo, Rossanto Dwi; Sugiharti, Lilik; Zargarr, Nasir Ahmad (Jurnal Ilmiah Manajemen & Bisnis, 2023)
This study seeks to examine the multidimensional poverty in Jammu and Kashmir, aiming to illuminate its nature and extent beyond traditional monetary measures. Utilizing the Alkire Foster method and drawing on data from NFHS-5, the research uncovers a prevalence of multidimensional poverty surpassing that of monetary poverty in the region. Within surveyed districts, the study identifies Ramban as experiencing the highest incidence, contrasting with Srinagar, which exhibits the lowest headcount. Anantnag emerges as the district facing the most intense multidimensional poverty. In exploring the factors influencing multidimensional poverty, binary logistic regression reveals the significant roles of education, occupation, and land ownership. Conflict is identified as an amplifier of multidimensional poverty, and a predictive model achieves an accuracy rate of approximately 82.80%. The study underscores the critical importance of local factors in shaping poverty experiences, emphasizing the roles of nutrition, sanitation, housing, and education. Gender, age, and conflict are highlighted as pivotal determinants in the latter stages of the study. The research concludes with a managerial perspective, offering actionable insights for policy recommendations, development initiatives, and specific steps for government agencies and stakeholders. These proposed interventions aim to address identified determinants and contribute to the overarching goal of reducing poverty in Jammu and Kashmir.